Proses Pembentukan Self-Control sebagai upaya Pencegahan Relapse pada Pasien Rehabilitasi Narkoba - Syifa Nurlatifah; Nur Azizah (Journal of Society Counseling, 2026)
Drug abuse is a complex social problem that has widespread impacts on physical, psychological, social, and economic aspects of life. One of the main challenges in the rehabilitation process is the high risk of relapse, which is often influenced by low levels of individual self-control. This study aims to analyze the process of developing self-control as an effort to prevent relapse among rehabilitation patients at IPWL YPI Nurul Ichsan Al-Islami. This research employed a qualitative approach with a descriptive design. The subjects consisted of rehabilitation patients and counselors selected through purposive sampling. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and method triangulation. The results showed that the development of self-control occurs gradually and holistically, covering behavioral, cognitive, emotional, and spiritual aspects. This process is carried out through detoxification, mental and spiritual guidance, and the formation of positive habits. Rehabilitation programs such as individual counseling, group counseling, and religious guidance play a significant role in enhancing self-control. Supporting factors include internal motivation, family support, and a conducive rehabilitation environment, while inhibiting factors include negative environmental influences and unstable psychological conditions. In conclusion, self-control is a key factor in preventing relapse and is developed through a holistic approach integrating psychological and spiritual aspects.